Correlation Between Wavelet-Based Energy Parameter and Observational Damage Degrees for Gravity Design Building During the May 2018 Mayotte Seismic Crisis - Negulescu, Caterina; Roullé, Agathe (Frontiers in Built Environment, 2022)
Mayotte seismic crisis started on 10 May 2018, with a first felt earthquake, quickly followed by many others, that surprised inhabitants. Before 10 May 2018, Mayotte Island, part of the volcanic Comoros archipelago in the North Mozambique Channel of the Indian Ocean was not considered as a significantly seismically active area and hence the structures were designed without or, very recently with low seismic code. In this study, we pay particular attention to existing seismic records of earthquakes with magnitude greater than 5, and we try to establish their dangerousness for existing buildings. As the magnitude is not very large, it is difficult to observe and classify the slight to moderate damages using the drift parameter. It is for this reason that in this study we try to consider the shift of the inelastic period and the dissipated energy, estimated using wavelet transform, in order to estimate the damage. We have modeled a target building and calculated its dynamic response using as input the recordings of the 46 strongest earthquakes of the current crisis. The dynamic calculations were performed using open source finite element software, Opensees © Berkeley. We analyzed the dynamic response at the top of the building in terms of period of vibration, energy dissipated and drift. We used the 46 recordings from two different seismological stations in terms of site effects: YTMZ station, considered as rock and MILA station, which shows strong site effects and therefore the strongest recordings in terms of acceleration. We try to find a correlation between the wavelet energy dissipation and the observational damage degree or drift based damage degrees. We find out that about 25% of the 46 earthquakes selected on soils with site effects (MILA station) have building response parameters corresponding to degrees of damage D1 and D2 of the EMS-98 scale: Negligible to slight damage (no structural damage, slight non-structural damage) and Moderate damage (light structural damage, moderate non-structural damage).